Diagnostic Function of 3-Tesla Magnetic Resonance Imaging for the Assessment of Brachial Plexus Injury. Issue 3 (July 2020) - Hung, Nguyen Duy; Duc, Nguyen Minh; Xoan, Nguyen Thi; Doan, Ngo Van; Huyen, Tran Thi Thanh; Dung, Le Thanh
Background: This study aimed to evaluate the diagnostic function of 3-Tesla (T) magnetic resonance imaging (MRI) during the assessment of brachial plexus injury (BPI), in comparison with intraoperative findings. Methods: A retrospective study was performed on 60 patients (47 men and 13 women), who had clinical manifestations of BPI, underwent 3T MRI of the brachial plexus, and were surgically treated at the Viet Duc and Vinmec Times City hospitals, in Hanoi, Vietnam, from March 2016 to December 2019. Preganglionic and postganglionic lesion features were identified on MRI. The diagnostic function of MRI features for the determination of BPI was evaluated and correlated with intraoperative findings. Results: The root avulsion and pseudomeningocele preganglionic injuries were observed in 57% and 43% of MRIs, respectively, and were commonly observed at the C7 and C8 roots. Nerve disruption and never edema were observed in 47.56% and 33.53% of MRIs, respectively, and were commonly observed at the C5 and C6 roots. The sensitivity, specificity, accuracy, positive prognostic value, and negative prognostic value of 3T MRI were 64.12%, 92.90%, 80.33%, 87.50%, and 76.96%, respectively, for the diagnosis of total avulsion, and 68.52%, 83.33%, 80.67%, 47.44%, and 92.34%, respectively, for the diagnosis of nerve disruption. Conclusion: MRI offers valuable details regarding the location, morphology, and severity of both preganglionic and postganglionic injuries during the preoperative diagnosis of BPI. However, this modality played a moderate diagnostic role. Therefore, 3T MRI should be used as a supplemental evaluation, coupled with clinical tests and electromyography, to determine the most appropriate treatment strategies for BPI patients.